An Honest Day's Work for an Honest Day's Wage - CHARLES M. SCHWAB (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1920)
THE ENGINEERS have placed this great country of ours in a preeminent position with everything pertaining to manufacture, metallurgy, and the kindred arts. We are second to none in the world. We have a country which, another speaker has said, God has endowed with such riches in coal and natural resources as no other country in the world. But rich as these are, there is one thing greater; the sturdy character, energy, and integrity of its people, which will make these great resources an influence in the world's developments. Great as are these resources and the energy and integrity of our people, there is one problem of our .engineering, which I term human engineering, that is of far more importance than the creation of machines and methods, with which you have been so successful in the past. Of what value is the skillfully devised machinery, the complex process, unless manned and operated by people whose heart and soul are in sympathy with the work they are doing and who have before them the giving of a complete day's work for a day's pay?